Impact of Environmental Reporting on Financial Performance: Study of Global Fortune 500 Companies - Zamil, G. M. Shahariar; Hassan, Zubair (Indonesian Journal of Sustainability Accounting and Management, 2019)
This study examines the impact of environmental reporting on the financial performance of Fortune 500 firms from 2013 to 2017. It appraises financial performance by measuring three independent variables: reduction in greenhouse gas emissions, reduction in waste, and reduction in water consumption. While the target population comprised the top 100 CSR-reputed companies listed on Fortune 500, the sample size was determined to be 50 based on observations of 250 companies. The collected data were analyzed using descriptive statistics, correlation, and regression analysis. Findings indicated that reduction in nominated variables such as greenhouse gas emissions and water consumption had a positive and significant impact on financial performance, whereas that in another variable, i.e., waste, had a negative and significant impact on financial performance. Thereby, this study recommends that firms should adopt environment-friendly resources to attract stakeholders as well as save the planet. It also suggests that firms need to accord dedicated focus to environmental reporting to improve profitability.